Assessment of Gender-related Differential Item Functioning of Teacher-Made Chemistry test. - Elizabeth O. Ojo; Joshua O. Adeleke; Simeon O. Ariyo (African Journal of Behavioural and Scale Development Research, 2022)
A good item that will measure the intended domain is expected to be free of biases. But several studies have confirmed that some items in a test reveal biases due to a group of testees.. A generally acceptable analytical technique that can be used to discover biases in test items is the Differential Item Functioning (DIF) which Item Response Theory (IRT) offers to check differences in psychometric properties due to the groups that testees belong. Thus, this study used the DIF technique to detect gender biased items in a teacher made Chemistry test. BILOG-MG was employed using 350 (183 males and 167 females) students from 10 Senior secondary school Two (SSII), randomly drawn from Obio/Akpor Local Government Area of Port Harcourt, River State, Nigeria. The study showed that out of one hundred items, fifty-three items were biased. However, 26(49.1%) out of 53 were in favour of the female while 27(50.9%) were in favour of the male which confirmed biases. DIF is effective in detecting group biases of test items. The study concluded that Differential Item Functioning should always be used by scale developers before collating the final items for a test.